Is fiscal devaluation welfare enhancing? A model-based analysis - Stefan Hohberger; Lena Kraus (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2015)
Large trade imbalances have emerged as major policy challenges for the euro area within the last decade. As fiscal policy is the major macroeconomic policy instrument left with the individual member countries of EMU, fiscal devaluation is a highly debated policy tool to mimic the effects of an external devaluation by implementing a budgetary-neutral tax shift from direct to indirect taxes. This paper uses a two-region two-sector DSGE model with nominal wage and price rigidities to analyse the welfare effects of fiscal devaluation understood as tax shift from social security contributions for employers to value-added tax in a small open economy in monetary union. This paper finds that fiscal devaluation can stabilise excessive trade balance fluctuations but implies welfare losses for the average household. The results are robust to several sensitivity checks.
Keywords: E62; F32; F41; 330